(untitled) (Research, Society and Development, 2023)
Cone beam computed tomography (CBCT) is an imaging modality widely used in endodontics, since it provides three-dimensional images without superposition of structures. The maxillary central incisor usually presents a single root and one root canal, but anatomical variations can happen. The aim of the present paper is to report a high-resolution CBCT evaluation of an upper central incisor with root bifurcation. This paper shows a descriptive and qualitative assessment of high-resolution CBCT images for endodontic purposes. A 39-year-old male patient was referred to a radiologic clinic to acquire CBCT images of the right upper central incisor, as the referring clinician noticed an anatomical difference between the two upper central incisors on a panoramic radiograph and suspected of dens invaginatus. CBCT images were acquired in high resolution (voxel size of 0.08 mm) and a restricted field-of-view (4x4 cm). CBCT volume displayed an anatomical variation of the central incisor, which presented root bifurcation and two root canals, with a normal clinical crown. The present case report shows a rare diagnosis of a maxillary central incisor presenting bifurcated root with two root canals, and to the best of the authors’ knowledge, this is the first case report to present high-resolution CBCT images with disclosed acquisition protocols to diagnose a bifurcated central incisor. The documentation of unusual cases has great didact value and contributes to information propagation. In the present case, high-resolution CBCT allowed a detailed evaluation of both roots and root canals, facilitating the clinician’s diagnostic task.